PROBLEM BASED LEARNING IN MANAGEMENT AND CLINICAL ENGINEERING COURSE - Hamzaid, Nur Azah; Md Saaid, Mohd Faiz; Mansor, Shuhaibul Fadzly; Hamid, Azman (Journal of Technical Education and Training, 2012)
This paper addressed student perceptions and opinion of the problem based learning method, as well as the empirically collected data on students’ learning outcomes on a Biomedical Engineering course, i.e. Management and Clinical Engineering. Pure lecture delivery with absence of practical intervention was deemed insufficient to provide appropriate means to achieve the course objectives. Therefore, a Mock Company assignment was introduced in this course as a problem based learning application aimed to aid the achievement of the program outcome while improving the attainment of the course objectives. The students were divided into groups to form individual mock company. Each mock company formed their organization post for each member, and came up with a business plan for a new project to be presented for fund approval by the panels, made up of the course instructors and invited lecturers from the clinical engineering industry and hospital practitioners. The company discussion progress and performance were monitored by the instructors through the formal university e- learning platform throughout the semester with occasional response and suggestions. The panels identified the expected lack of business and management knowledge but this was counteracted by the reasonably successful business plan produced independently by all companies’ At the end of the semester, through questionnaires, 69.6% of the 56 students agreed that this mock company assignment was useful in achieving the course objectives and should be conducted in the following years. Students who performed weakly in this assignment also demonstrated lower performance in all evaluations including by traditional means (p = 0.01), although there were no direct associations amongst the problem-based and the traditional evaluations (r <0.66). The students’ responses also reflected their readiness to perform more independent learning approaches, despite them expressing the lack of clear scope and guideline, which is the nature of a problem-based learning experience.